Pyhtocosmetics in Pharmacy - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2015)
The increased desire among individuals to live a comfortable life, to be healthy, beautiful and groomy with developing world order; allows cosmetics and dermocosmetics industry to rapidly develop and increases the demand for their use. In recent years, increased interest among people to natural products instead of synthetic chemicals in every issue, especially to herbal forms, led to an increase of phytocosmetics within the cosmetics sector. The plants, plant oils and extracts practiced with simple methods to stay young and become beautiful for centuries, have begun to take part in phytocosmetics products nowadays. As they are being preferred, their number and varities are increasing each day. Although not many scientific research is available regarding phytocosmetics products and most preferred plants in the industry, day by day increasing demand to these products attracts researchers' attention and directs them to research more on the issue. In our research, to contribute the areas of cosmetics, dermocosmetics and phytocosmetics; we aimed to identify the phytocosmetic products and plants within the composition of these products, present in the pharmacies of the Anatolian side of Istanbul. According to our research, ten most widely used plants are identified as; Butyrospermum parkii (118), Vitis vinifera (106), Helianthus annuus (103), Olea europaea (91), Glycine max (82), Rosmarinus officinalis (80), Simmondsia chinensis (76), Citrus aurantium var. dulcis (Citrus sinensis) (75), Aloe barbadensis (69), Citrus medica var. limonum (68).
Keywords: Cosmetic; Dermocosmetic; Phytocosmetic; Plant; Pharmacy